Detection of gustatory and olfactory disorders as a screening criterion for the identification of patients in the early stages of COVID-19 reinfection - Trentin-Bordignon, Natalia Cristina; Gondak, Rogério (Journal of Oral Diagnosis, 2021)
Introduction: Variants of SARS-COV-2 have been detected and presented new capacities of infection and transmissibility, compromising the pandemic trajectory. Furthermore, chemosensory dysfunction are common symptoms of COVID-19. Objective: We aimed to provide a brief information of the current knowledge regarding chemosensory manifestations are common symptoms of COVID-19. Material and Methods: Due to the possibility of a higher incidence of the new covid-19 variants, we evaluated some studies published in the literature considering the analysis of smell and taste disorders as a criteria for the early diagnosis of positive patients and their immediate isolation. Results: Considering the economic limitations of many countries for the acquisition of results promptly by RT-PCR and immunization coverage, the evaluation of olfactory and gustatory disorders during COVID-19 outbreak can be useful tool to guide immediate isolation of the patient until the result of the laboratory test, contributing for the prevention of the virus spreading. Conclusion: As gustatory disorders are strong predictors of infection by COVID-19, health professionals should be alert for these symptoms having an important role as a screening criterion and early diagnosis.